Ischemic Posterior Circulation Stroke: A Review of Anatomy, Clinical Presentations, Diagnosis, and Current Management - Nouh, Amre; Remke, Jessica; Ruland, Sean (Frontiers in Neurology, 2014)
Posterior circulation (PC) strokes represent approximately 20% of all ischemic strokes. In contrast to the anterior circulation (AC) several differences in presenting symptoms, clinical evaluation, diagnostic testing and management strategy exist which may present a challenge to the treating physician. This review will discuss the anatomical, etiological and clinical classification of PC strokes, identify diagnostic pitfalls and overview current therapeutic regimens.